2011
DOI: 10.1017/s1041610211000779
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine and cognitive decline in older hypertensive subjects

Abstract: In a population of older hypertensive patients, higher plasma homocysteine was associated with cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Previous reports revealed that elevated Hcy levels may be an independent risk factor for cognitive impairment. Higher Hcy levels have been found to be associated with more serious degrees of cognitive impairment [27,28]. A novel treatment targeting Hcy via a high dose of supplementary B vitamins might decrease the accelerated rate of brain atrophy in MCI [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed that elevated Hcy levels may be an independent risk factor for cognitive impairment. Higher Hcy levels have been found to be associated with more serious degrees of cognitive impairment [27,28]. A novel treatment targeting Hcy via a high dose of supplementary B vitamins might decrease the accelerated rate of brain atrophy in MCI [29].…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence indicating that hHcys contributes to the development of a number of degenerative or sclerotic diseases including coronary artery disease, multiple sclerosis, Parkinson’s disease and many complications associated with aging in general, like osteoporosis and cognitive decline [4, 3943]. Elevated levels of this methionine amino acid intermediate have also been considered to be an independent risk factor for chronic renal disease, promoting glomerular dysfunction and end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma concentrations of homocysteine have been shown to be associated with poor cognitive function, cognitive decline and dementia [3,4]. High plasma homocysteine concentration has been associated with silent brain infarcts and atherosclerosis causing cognitive impairment [5,6], and activation of Nmethyl-D-aspartate receptors resulting in neuronal cell damage and hippocampal atrophy [6].…”
Section: Introductionmentioning
confidence: 99%